Peramalan Penjualan Produk Sepatu dengan Menggunakan Metode Double Moving Average (DMA) - Dandi Irwansyah; Jeperson Hutahaean; Suparmadi Suparmadi (Forum Kerjasama Pendidikan Tinggi, 2022)
Halim Jaya Kisaran shop is one of the trading businesses that sells people's basic needs such as shoes and bags. This store requires forecasting in an effort to process data and generate accurate reports. This is done because the Halim Jaya Kisaran Store to determine the demand for shoes is unpredictable, so it often experiences a lack of shoes to be purchased in order to serve the demand for shoes needed by customers. In designing this system, the author uses the Double Moving Average (DMA) forecasting method for the decision support process in determining the number of shoe stocks to be sold for the next month, using the calculation method. This forecasting application was created using the Visual Basic Net 2010 programming language with Microsoft Access as the database. From making the system an application can be produced that can control optimal and economical demand and with a high level of accuracy and can predict the number of shoe requests at the Halim Jaya Kisaran Store so that the forecast results can help the store to avoid running out of stock of shoe requests at the Halim Jaya Kisaran Store